PENYULUHAN PEMILAHAN SAMPAH DI KELURAHAN KAMPUNG JAWA KOTA SOLOK - Widya Bestari; Taufiq Ihsan (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Along with population growth and the development of human activities have implications for the generation of waste. Therefore, in order to anticipate, it is necessary to learn from an early age related to waste sorting. No exception in Kampung Jawa as a dense urban village in Solok City. The purpose of this activity is to increase public awareness, namely elementary school students, towards waste. The activity was carried out at SDN 11 Kampung Jawa Village, Solok City. The selection of the target object is based on the consideration that concern for waste problems must be generated from an early age and children must be taught how to sort waste properly and correctly. This activity was carried out in Kampung Jawa, Tanjung Harapan District, Solok City, West Sumatra Province. The method of carrying out activities is the lecture method, simulation, and gift giving. The result of the activity is that students can explain and succeed in sorting waste, and throwing it in the trash according to its designation. With this activity, in the long term it is hoped that the waste problem can be minimized. Garbage has been disposed of in the trash according to its type so as to facilitate the process of waste management and processing. It is hoped that this activity can raise awareness of the people of Kampung Jawa, not only elementary school students but also parents and teachers. It is recommended to conduct regular monitoring to evaluate the activities that have been carried out in Kampung Jawa Village, Solok City.